Teatro científico : uma ferramenta didática para o ensino de Física - Gimenez, Hercules (2013)
This thesis presents the results of an educational research developed in the State School “Professora Maria de Fátima Gimenez Lopes” at Sinop, Mato Grosso, with two classes of elementary school students during the school year 2012. Our work, based on the meaningful learning, proposed the theater as a teaching instrument for the teaching of natural science, looking for a reflection about their potential in the (re)construction of physics concepts through reading and dramatization of texts about History and Philosophy of Science. The theater play “Shoulders of Giants” based on the screenplay adapted from the play “Galileo Life” written by Bertold Brecht, was produced from a readings commented program, productions of texts, researches and debates. During the work, we establish an affective experience between students and teachers, creating an appropriate environment to the meaningful learning in the classroom, where the members of the group could develop attitudes of cooperation, mutual respect, complicity, friendship, among others. The experience gave us some satisfactory results about the possibilities for teaching and learning physics through dramaturgy. We realized that the students involved in the project improved the quality of their relationships with the knowledge, teachers and classmates. They saw themselves as subject (co)responsible for their learning, while authors of the play and at the same time publishers of scientific knowledge as actors, supporting our idea that the theater can be a teaching instrument that offers significant learning of physics concept to the students and the level shift of school learning to another higher.